Married women's employment and motherhood employment penalty by couple's educational attainments across 10 countries - Ji Young Kang; Wonjin Lee; Sunyu Ham; Julia Shu-Huah Wang (Luxembourg Income Study (LIS), 2022)
This study examines how and to what extent a couple's education is associated with married women's employment and the motherhood penalty in 10 countries. We use data from the Luxembourg Income Study and the Korean Labor & Income Panel Study (2013). Overall, Denmark and Norway show the highest level of married women's employment and no motherhood penalty. Our findings support the opportunity cost perspective, in general, that highly educated women are more likely to participate in work than less educated women, except in Germany, Korea, and Japan. The social capital and gender-egalitarian perspectives hold for the United States and Italy. We also find significant variation in married women's employment in East Asian countries. Married Korean women are less likely to be employed than in China and Taiwan, while Japanese women are the least employed among husband high - wife high education couples.
Keywords: 330; married women's employment; motherhood penalty; education